P34 No effect of tenofovir or entecavir on vitamin D levels in Chronic Hepatitis B mono-infected patients. Single centre 'real life' cohort experience. (6th September 2011) - Nguyen, H-L; Carey,; Al-Freah, M A B; Joe, D; Sherwood, R; Knighton, S; Harrison, P; Suddle, A; Agarwal, K
Abstract : Introduction: Increasing evidence confirms the pivotal role of Vitamin D in immunomodulatory and metabolic processes. Vitamin D deficiency has an impact on long-term health outcomes. Data from HIV populations demonstrate negative effects of Tenofovir (TDF) on vitamin D (VD) levels and bone mineral density. Aim: To determine the impact of TDF on VD levels, with calcium and phosphate in patients mono-infected with HBV. Method: Retrospective study of all patients treated with TDF. VD (μg/l), phosphate (PO4, mmol/l), calcium (Ca 2+, mmol/l) and alkaline phosphatase (ALP, IU/l) were checked at baseline, and 12 months after TDF or Entecavir (ETV) exposure. Results: Patients with complete data were analysed (n=313), 22 patients were excluded because of combination treatment TDF and ETV. There were 212 patients (73%) treated with TDF and 79 (27%) treated with ETV. Median age was 42 years (19–80); 266 (72%) were Male. African-Caribbeans represented 49% and South East Asians represented 24%. There were 14 patients (5%) with hepatocellular carcinoma (HCC) and 9 (3.1) patients post liver transplantation. Median AST was 30 (12–328), Bilirubin 11 (3–148), INR 1.05 (0.88–2.47) and albumin 44 (24–73). Prevalence of VD deficiency (VD <22  μg/l) in patients who had VD checked at baseline (n=192) was 81.3%. Distribution of VD deficiency was not significantly different based on ethnicity (p=NS), however, VD deficiency was more prevalent among men (85% vs 72%, p=0.034). 70/212 (33%) of those treated with TDF had VD supplements compared to 4/79 (5.1%) of ETV group, p<0.001. These patients were excluded from paired comparisons of VD over 12 months after TDF or ETV exposure. In TDF treated patients, median VD was 14.2 (0–49) at baseline and 14.7 (0–41) 12 months of therapy, p=NS. There was no significant difference in median Ca 2+ (2.24 vs 2.23, p=NS), PO4 (0.99 vs 1.04, p=NS), however, ALP significantly increased after 12 months of TFV treatment (71.5 vs 75, p<0.05). Patients treated with ETV monotherapy, median VD at baseline was 16.1 (6–50) and after 12 months of ETV treatment was 13.6 (4.2–43.5), p=NS. No significant difference was found between baseline and 12 months Ca 2+ (2.25 vs 2.23), PO4 (0.91 vs 0.96) or ALP (70 vs 68), p=NS for all comparisons. Abstract P34 table 1 demonstrate demographic, clinical and bone markers of TDF and ETV treated patients at baseline and after 12 months of therapy. TDF group had significantly lower male prevalance and AST, but a significantly increased proportion of patients with HCC, baseline and 12 months PO4 and ALP at 12 months. Conclusion: VD deficiency is highly prevalent in this cohort of CHB patients and should be appropriately identified and treated. TDF and ETV treatment had no significant effect on VD levels after 12 months of treatment in this cohort. However, there was significant rise in PO4 and ALP after 12 months of TDF treatment; which may infer indirect longer effects on bone metabolism.